Expanding hot flow in the black hole binary SWIFT J1753.5-0127: evidence from optical timing - Veledina A; Gandhi P; Hynes R; Kajava JJE; Tsygankov SS; Revnivtsev MG; Durant M; Poutanen J (OXFORD UNIV PRESS, 2022)
We describe the evolution of optical and X-ray temporal characteristics during the outburst decline of the black hole X-ray binary SWIFT J1753.5-0127. The optical/ X-ray crosscorrelation function demonstrates a single positive correlation at the outburst peak, then it has multiple dips and peaks during the decline stage, which are then replaced by the precognition dip plus peak structure in the outburst tail. Power spectral densities and phase lags show a complex evolution, revealing the presence of intrinsically connected optical and X-ray quasi-periodic oscillations. For the first time, we quantitatively explain the evolution of these timing properties during the entire outburst within one model, the essence of which is the expansion of the hot accretion flow towards the tail of the outburst. The pivoting of the spectrum produced by synchrotron Comptonization in the hot flow is responsible for the appearance of the anticorrelation with the X-rays and for the optical quasi-periodic oscillations. Our model reproduces well the cross-correlation and phase lag spectrum during the decline stage, which could not be understood with any model proposed before.